A Theory of Linear Profit-Sharing Incentives - Berhold, Marvin (Quarterly Journal of Economics, 1971)
I. Introduction to the general model, 460. —II. The problem of contractual incentives, 466. — III. Factors affecting the selection of an optimal incentive function, 470. —IV. Variation in the utility functions, 477. —V. Extension of results to Case II and Case II, 480. —VI. Government incentive contracts as a special case of the linear profit-sharing model, 480.—VII. Summary and conclusions, 481.